Localization of rural communities near environmental liabilities and bodies of water. - César Julio Cáceda Quiroz (22683324) (2025)
Sample site: Tutupaca, Yucamane, Cano, Chulluncane, Cercana. Rural Communites: C.C. Turunturo and C.C. Palca.